2015
DOI: 10.1186/s12889-015-1406-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cardiovascular disease risk using waist circumference among Aboriginals in a remote Australian community

Abstract: BackgroundElevated waist circumference (WC) is an important risk factor for cardiovascular disease (CVD). Aboriginals in Australia are at higher risk of CVD compared to non-Aboriginals. We examined the association between waist circumference and CVD, and developed a model for projecting absolute risk of cardiovascular disease using WC and age in one high risk Australian Aboriginal community.MethodsWe followed up 920 (470 men, 450 women) participants (more than 80% of the eligible population) aged 18 to 76 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Several studies have shown that the equations derived from the Framingham study underestimate the CVD risk of Indigenous Australians [10,11]. One explanation for this underestimation may be that certain CVD risk factors for Indigenous people such as albuminuria and waist circumference are not included in the Framingham CVD equations [2,3,12,13]. While it is possible to recalibrate the Framingham models to correct for this underestimation [11], this does not account for a broader range of risk factors which are potentially useful in further stratifying risk.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the equations derived from the Framingham study underestimate the CVD risk of Indigenous Australians [10,11]. One explanation for this underestimation may be that certain CVD risk factors for Indigenous people such as albuminuria and waist circumference are not included in the Framingham CVD equations [2,3,12,13]. While it is possible to recalibrate the Framingham models to correct for this underestimation [11], this does not account for a broader range of risk factors which are potentially useful in further stratifying risk.…”
Section: Introductionmentioning
confidence: 99%
“…Our choice of WC as a measure of adiposity was based on previous findings from recent studies in the same study population suggesting WC is a better predictor of CVD compared with BMI and WHR (155). Second, the prospective nature of our study enabled calculating absolute risk based on future CVD events which provided proof of the WC values generated from BMI points (115).…”
Section: Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
“…For Males: (155). In the present study, the absolute risk method was employed to generate WC values from BMI with equivalent absolute CVD risk.…”
Section: Cardiovascular Diseases (Cvd)mentioning
confidence: 99%
See 2 more Smart Citations